Celastrus-derived Celastrol Suppresses Autoimmune Arthritis by Modulating Antigen-induced Cellular and Humoral Effector Responses - Venkatesha, Shivaprasad H. (American Society for Biochemistry and Molecular Biology, 2011)
Rheumatoid arthritis (RA) is an autoimmune disease characterized by synovial inflammation and articular damage. Proinflammatory cytokines, antibodies, and matrix-degrading enzymes orchestrate the pathogenic events in autoimmune arthritis. Accordingly, these mediators of inflammation are the targets of several anti-arthritic drugs. However, the prolonged use of such drugs is associated with severe adverse reactions. This limitation has necessitated the search for less toxic natural plant products that possess anti-arthritic activity. Furthermore, it is imperative that the mechanism of action of such products be explored before they can be recommended for further preclinical testing. Using the rat adjuvant-induced arthritis model of human RA, we demonstrate that celastrol derived from Celastrus has potent anti-arthritic activity. This suppression of arthritis is mediated via modulation of the key proinflammatory cytokines (IL-17, IL-6, and IFN-γ) in response to the disease-related antigens, of the IL-6/IL-17-related transcription factor STAT3, of antibodies directed against cyclic citrullinated peptides and Bhsp65, and of the activity of matrix metalloproteinase-9 and phospho-ERK. Most of the clinical and mechanistic attributes of celastrol are similar to those of Celastrus extract. Several studies have addressed the antitumor activity of celastrol. Our study highlights the anti-arthritic activity of Celastrus-derived celastrol and the underlying mechanisms. These results provide a strong rationale for further testing and validation of the use of celastrol and the natural plant extract from Celastrus as an adjunct (with conventional drugs) or alternative modality for the treatment of RA.